Edward Said : Legacy of a Public Intellectual. - Ganguly, Debjani (Melbourne University Publishing, 2015)
This collection is an enterprise of discovery and critical inquiry into the legacy of one of late modernity's greatest public intellectuals, Edward Said. Noted contributors, including Bill Ashcroft, John Docker, Lisa Lowe, Hsu-ming Teo and Patrick Wolfe, address an array of intellectual, political and cultural issues in their engagement with Said's oeuvre.